Investigating the Therapeutic Potential of AMP-Activated Protein Kinase in Myotonic Dystrophy Type 1 - Misquitta, Naomi (Université d'Ottawa | University of Ottawa, 2024)
Myotonic dystrophy type 1 (DM1) is the most prevalent form of adult-onset muscular dystrophy and arises from a CTG trinucleotide repeat expansion mutation in the dystrophia myotonica protein kinase (DMPK) gene. Mutant DMPK mRNAs accumulate as nuclear foci and cause disruptions in pre-mRNA processing via a toxic gain-of-function mechanism that involves the misregulation of key RNA-binding proteins, such as muscleblind-like splicing regulator 1 (MBNL1). These misregulations result in perturbations in pre-mRNA alternative splicing, amongst other cellular processes, which promote skeletal muscle impairments and give rise to several clinical features of DM1 including weakness, wasting, and myotonia. To date, there is no cure for DM1. AMP-activated protein kinase (AMPK) signaling is a key regulator of skeletal muscle plasticity that was initially revealed by the Jasmin Laboratory to be impaired in a mouse model of DM1. Our lab also demonstrated that potent AMPK activators, AICAR and exercise, improve the disease phenotype in DM1 mouse skeletal muscles. Here, we examined the combinatorial impact of these AMPK agonists on the DM1 skeletal muscle phenotype. Our findings revealed that, in combination, 4 weeks of swimming exercise and AICAR treatment additively mitigate the nuclear accumulation of toxic RNA foci and promote muscle fiber hypertrophy in the skeletal muscles of female DM1 mice. These combinatorial effects were accompanied by a concomitant reduction in both the misregulation of MBNL1 and aberrant alternative splicing of key pre-mRNA targets. Altogether, these results highlight the therapeutic potential of combining AMPK-based interventions for the treatment of DM1.
Keywords: Myotonic dystrophy type 1; Skeletal muscle